Development of biocatalysts for production of commodity chemicals from lignocellulosic biomass - Adsul, Mukund G.; Singhvi, M. S.; Gaikaiwari, Shalaka A.; Gokhale, D. V. (Bioresource Technology, 2011)
Lignocellulosic biomass is recognized as potential sustainable source for production of power, biofuels and variety of commodity chemicals which would potentially add economic value to biomass. Recalcitrance nature of biomass is largely responsible for the high cost of its conversion. Therefore, it is necessary to introduce some cost effective pretreatment processes to make the biomass polysaccharides easily amenable to enzymatic attack to release mixed fermentable sugars. Advancement in systemic biology can provide new tools for the development of such biocatalysts for sustainable production of commodity chemicals from biomass. Integration of functional genomics and system biology approaches may generate efficient microbial systems with new metabolic routes for production of commodity chemicals. This paper provides an overview of the challenges that are faced by the processes converting lignocellulosic biomass to commodity chemicals. The critical factors involved in engineering new microbial biocatalysts are also discussed with more emphasis on commodity chemicals. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biomass utilization; Commodity chemicals; Ethanol; Lactic acid; Microbial cellulases

Differential induction, purification and characterization of cold active lipase from Yarrowia lipolytica NCIM 3639 - Yadav, K. N. Sathish; Adsul, Mukund G.; Bastawade, Kulbhushan B.; Jadhav, D. D.; Thulasiram, H. V.; Gokhale, D. V. (Bioresource Technology, 2011)
The production, purification and characterization of cold active lipases by Yarrowia lipolytica NCIM 3639 is described. The study presents a new finding of production of cell bound and extracellular lipase activities depending upon the substrate used for growth. The strain produced cell bound and extracellular lipase activity when grown on olive oil and Tween 80, respectively. The organism grew profusely at 20 degrees C and at initial pH of 5.5, producing maximum extracellular lipase. The purified lipase has a molecular mass of 400 kDa having 20 subunits forming a multimeric native protein. Further the enzyme displayed an optimum pH of 5.0 and optimum temperature of 25 degrees C. Peptide mass finger printing reveled that some peptides showed homologues sequence (42%) to Yarrowia lipolytica LIP8p. The studies on hydrolysis of racemic lavandulyl acetate revealed that extracellular and cell bound lipases show preference over the opposite antipodes of irregular monoterpene, lavandulyl acetate. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cell bound lipase; Cold active lipase; Extracellular lipase; Lavandulyl acetate; Oligomeric lipase